Value Sets for EQ-5D-5L A Compendium, Comparative Review & User Guide - Devlin, Nancy; Roudijk, Bram; Ludwig, Kristina (Springer Nature, 2022)
This open access book provides an essential guide to value sets for anyone working with EQ-5D-5L data. The EQ-5D-5L is one of the most widely used health related quality of life questionnaires around the world, with applications in clinical trials, population health surveys and routine outcomes measurement. In addition to providing a concise, generic way of describing health, the EQ-5D-5L facilitates the valuation of health and health improvements through its value sets, which play a pivotal role in Health Technology Assessment across the world. Value sets for the EQ-5D-5L have been produced in a wide range of countries and regions, using a standardised international protocol developed by the EuroQol Group. This book brings together, for the first time, a comprehensive inventory of these value sets and a comparative review of their characteristics. In addition to the structured summaries of each value set, the book provides clear guidance to users and researchers on how to choose which value set to use, for what purpose. It also provides information about the methods that were used to produce these values, how these methods have been refined and how they may evolve in future. The book is the culmination of a substantial programme of work internationally. By collating these value sets into a single volume, the book aims to provide an easy-to-use resource which is likely to become a key reference source for EQ-5D-5L users and researchers.